A hydrocracking catalyst for bicyclic aromatic hydrocarbons, and a preparation method and application thereof
Patent Information
- Application Number
- CN202210613270.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-31
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-05-31
AI Technical Summary
[0007]上述专利文献中提到的分子筛虽然能够获得具有较高芳烃含量的加氢裂化产物,但对于双环芳烃转换率仍有待提高
[0022] Through the above technical solution, this disclosure achieves screening through N value, and uses novel molecular sieves or related combinations as catalysts for acidic components, which can improve the conversion rate of feedstock oil with bicyclic aromatic content, and is used in the process of hydrocracking of inferior diesel to produce high cetane diesel or light aromatics.
Smart Images

Figure BDA0003672621140000091 
Figure BDA0003672621140000101 
Figure BDA0003672621140000102
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of catalysts, and more specifically, to a hydrocracking catalyst for bicyclic aromatic hydrocarbons, its preparation method, and its application. Background Technology
[0002] With increasingly stringent emission standards for automotive diesel fuel, lower aromatic content and control of total aromatics are required. The quality of catalytic cracking diesel fractions is deteriorating, characterized by high aromatic content and low cetane number, making them unsuitable as diesel feedstock. Based on the composition of catalytic diesel fuel rich in bicyclic aromatics and the reaction characteristics of bicyclic aromatic hydrocracking, research on the hydroretrogradation and cracking of catalytic diesel fuel to produce high-cetane-number diesel fuel or light aromatics has received widespread attention. The catalyst is the core of this technology. Selecting a suitable molecular sieve is the first step in catalyst design; without a good microporous structure as a support, no amount of subsequent adjustments may yield a satisfactory molecular sieve.
[0003] In existing technologies, the use of Y-type and Beta-type molecular sieve catalysts is frequently reported, for example:
[0004] Chinese patent document CN105457671B discloses a hydrocracking catalyst, its preparation method, and a method for hydrocracking reaction. The hydrocracking catalyst comprises a support and an active component supported on the support, wherein the active component is composed of molybdenum, cobalt, and nickel. The solid acid component is a Y-type molecular sieve or a mixture of a Y-type molecular sieve and amorphous silica-alumina.
[0005] Chinese patent document CN105457672 discloses a hydrocracking catalyst, its preparation method, and a method for hydrocracking reaction. The hydrocracking catalyst comprises a support and an active component loaded on the support, wherein the active component is composed of molybdenum, cobalt, and nickel. The solid acid component is a Beta zeolite molecular sieve or a mixture of Beta zeolite molecular sieve and amorphous silica-alumina.
[0006] Chinese patent document CN101618334 discloses an in-situ molecular sieve hydrocracking catalyst and its preparation method. The in-situ molecular sieve hydrocracking catalyst contains a hydrocracking active metal component and a cracking active component. The cracking active component includes a Y-type molecular sieve synthesized in situ. The in-situ molecular sieve cracking component accounts for 10% to 90% of the weight of the hydrocracking catalyst, and the specific surface area of the hydrocracking catalyst is 150 to 500 μm. 2 The catalyst has a pore volume of 0.2–0.4 mL / g, with mesopores of 2–10 nm accounting for more than 40% of the total pore volume. The catalyst is prepared using a conventional impregnation method.
[0007] Although the molecular sieves mentioned in the aforementioned patent documents can obtain hydrocracking products with high aromatic content, the conversion rate of bicyclic aromatics still needs to be improved. Summary of the Invention
[0008] The purpose of this disclosure is to improve the catalyst's adsorption capacity for reactant molecules, increase the conversion rate of bicyclic aromatic hydrocarbons, and thus achieve the maximum conversion of bicyclic aromatic hydrocarbons.
[0009] To achieve the above objectives, the first aspect of this disclosure provides a hydrocracking catalyst for bicyclic aromatic hydrocarbons, the hydrocracking catalyst comprising a support and an active metal component supported on the support; the active metal component comprising Group VIII metal elements and Group VIB metal elements; the support being composed of an acidic component and a matrix, the acidic component being a molecular sieve with an N value greater than 1;
[0010] The N value of a certain molecular sieve to be tested is defined as the ratio of the amount of bicyclic aromatic hydrocarbons and their derivatives adsorbed by the molecular sieve to the amount of bicyclic aromatic hydrocarbons and their derivatives adsorbed by the standard molecular sieve. The standard molecular sieve is HY molecular sieve, and the molar ratio of SiO2 to Al2O in the standard molecular sieve is 5.4, and the cell constant is 24.60 Å.
[0011] Optionally, the N value of the molecular sieve is 1-100, preferably 1-20; optionally, the pore volume of the molecular sieve is 0.4-0.8 cm³. 3 / g, acid density is 0.8-2.5μmol / m 2 .
[0012] Optionally, based on the total weight of the carrier, the content of the acidic component is 5-60% by weight, preferably 10-45% by weight; and the content of the matrix is 40-95% by weight, preferably 55-90% by weight.
[0013] Optionally, based on the total weight of the catalyst and calculated as oxides, the hydrocracking catalyst contains 1-10% by weight of Group VIII metals and 2-40% by weight of Group VIB metals; preferably, the hydrocracking catalyst contains 1-6% by weight of Group VIII metals and 5-35% by weight of Group VIB metals.
[0014] Optionally, the molecular sieve is selected from at least one of ITQ-40 molecular sieve, ITQ-44 molecular sieve, ITQ-37 molecular sieve, ITQ-53 molecular sieve, ITQ-54 molecular sieve, OSB-1 molecular sieve, and EMC-2 molecular sieve.
[0015] Optionally, the matrix is selected from at least one of alumina, silicon oxide, and silicon oxide-alumina.
[0016] A second aspect of this disclosure provides a method for preparing a hydrocracking catalyst, the method comprising:
[0017] S1. The matrix and molecular sieve are mixed, kneaded, and extruded to obtain an extruded strip; the extruded strip is subjected to a first drying and a first calcination to obtain a carrier;
[0018] S2. Impregnate the carrier with an aqueous solution of a compound containing a Group VIII metal and a Group VIB metal to obtain an impregnated carrier; subject the impregnated carrier to a second drying and a second calcination.
[0019] Optionally, the weight ratio of the matrix to the molecular sieve is 5-60:40-95.
[0020] Optionally, in step S1, the conditions for the first drying treatment include: a drying temperature of 80-300℃, preferably 100-200℃; and a drying time of 1-12 hours, preferably 2-8 hours; the conditions for the first calcination include: a calcination temperature of 350-850℃, preferably 450-650℃; and a calcination time of 1-12 hours, preferably 2-6 hours; in step S2, the conditions for the impregnation include: an impregnation temperature of room temperature -150℃; and an impregnation time of 1-6 hours; the conditions for the second drying include: a temperature of 100-300℃, preferably 100-150℃; and a time of 2-8 hours; and the conditions for the activation treatment include: a temperature of 100-350℃, preferably 120-250℃; and a time of 1-12 hours, preferably 2-6 hours.
[0021] A third aspect of this disclosure provides a method for removing aromatics from a diesel fraction, the method comprising: contacting the diesel fraction and hydrogen with the aforementioned hydrogenation catalyst and performing a hydrocracking reaction.
[0022] Through the above technical solution, this disclosure achieves screening through N value, and uses novel molecular sieves or related combinations as catalysts for acidic components, which can improve the conversion rate of feedstock oil with bicyclic aromatic content, and is used in the process of hydrocracking of inferior diesel to produce high cetane diesel or light aromatics.
[0023] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Detailed Implementation
[0024] The following provides a detailed description of specific embodiments of this disclosure. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of this disclosure.
[0025] The first aspect of this disclosure provides a hydrocracking catalyst for bicyclic aromatic hydrocarbons, the hydrocracking catalyst comprising a support and an active metal component supported on the support; the active metal component comprising Group VIII metal elements and Group VIB metal elements; the support is composed of an acidic component and a matrix, the acidic component being a molecular sieve with an N value greater than 1;
[0026] The N value of a certain molecular sieve to be tested is defined as the ratio of the amount of bicyclic aromatic hydrocarbons and their derivatives adsorbed by the molecular sieve to the amount of bicyclic aromatic hydrocarbons and their derivatives adsorbed by the standard molecular sieve. The standard molecular sieve is HY molecular sieve, and the molar ratio of SiO2 to Al2O in the standard molecular sieve is 5.4, and the cell constant is 24.60 Å.
[0027] The inventors of this disclosure have discovered that the properties of the acidic component molecular sieve affect the hydrogenation saturation and ring-opening properties of aromatics, as well as their cracking performance, thereby affecting the conversion rate of aromatics in the catalytic diesel hydrocracking process. This disclosure achieves screening through N-value, using novel molecular sieves or related combinations as catalysts for the acidic component. This can significantly improve the conversion rate of feedstock oils with high bicyclic aromatic content, making it suitable for use in the hydrocracking of low-quality diesel to produce high-cetane diesel or light aromatics.
[0028] In this disclosure, the N value is determined by an adsorption molar ratio test method, specifically as follows: First, accurately measure 100 mL of tetrahydronaphthalene solution (at room temperature), then add a quantitative amount of molecular sieve material (5 g), and stir under an inert gas (N2) atmosphere at 1 atm for 360°C for 10 hours. Then filter, re-adjust the filtrate to the correct volume, cool to room temperature, and measure the solution volume again using a graduated cylinder to obtain the adsorption volume difference ΔV. 测试分子筛 The formula for calculating N is:
[0029] N=(ΔV 测试分子筛* M 测试分子筛 ) / (ΔV Y型分子筛* M Y型分子筛 )
[0030] Where ΔV 测试分子筛 ΔV Y型分子筛 To test the volume difference in adsorption of tetrahydronaphthalene between molecular sieves and Y-type molecular sieves, M 测试分子筛 M Y型分子筛 To test the molar mass of molecular sieves and Y-type molecular sieves.
[0031] In a preferred embodiment of this disclosure, the N value of the molecular sieve can be 1-100, preferably 1-20; optionally, the pore volume of the molecular sieve can be 0.4-0.8 cm³. 3 / g, acid density can be 0.8-2.5μmol / m 2 .
[0032] According to this disclosure, based on the total weight of the carrier, the content of the acidic component can be 5-60% by weight, preferably 10-45% by weight; the content of the matrix can be 40-95% by weight, preferably 55-90%.
[0033] According to this disclosure, based on the total weight of the catalyst and calculated as oxides, the hydrocracking catalyst may contain 1-10% by weight of Group VIII metals and 2-40% by weight of Group VIB metals; preferably, the hydrocracking catalyst may contain 1-6% by weight of Group VIII metals and 5-35% by weight of Group VIB metals.
[0034] According to this disclosure, the molecular sieve may be selected from at least one of ITQ-40 molecular sieve, ITQ-44 molecular sieve, ITQ-37 molecular sieve, ITQ-53 molecular sieve, ITQ-54 molecular sieve, OSB-1 molecular sieve and EMC-2 molecular sieve.
[0035] According to this disclosure, the matrix can be selected from at least one of alumina, silicon oxide, and silicon-alumina. The alumina described in this disclosure is selected from one or more transition phase alumina of γ, η, θ, δ, and χ, or it can be alumina containing one or more transition phase alumina of γ, η, θ, δ, and χ selected from silicon, titanium, magnesium, boron, zirconium, thorium, niobium, and rare earth additives, preferably γ-alumina and γ-alumina containing one or more γ-alumina selected from silicon, phosphorus, titanium, magnesium, boron, zirconium, thorium, niobium, and rare earth additives. These can be commercially available or obtained using any existing method. The silicon-alumina is preferably a silicon-alumina having a pseudo-boehmite structure, and can also be a commercially available product or prepared using any existing technology. For example, the Siral series of commercially available silicon-alumina products manufactured by Condea GmbH in Germany have a pseudo-boehmite structure and can be used in this disclosure.
[0036] The catalyst provided in this disclosure can be used to carry out the reaction in any reactor capable of bringing the feedstock into contact with the catalyst under hydrotreating conditions, for example, in a fixed-bed reactor, a moving-bed reactor, or a fluidized-bed reactor. Other types of hydrocarbon feedstocks can also be directly processed for hydrotreating.
[0037] A second aspect of this disclosure provides a method for preparing a hydrocracking catalyst, the method comprising:
[0038] S1. The matrix and molecular sieve are mixed, kneaded, and extruded to obtain an extruded strip; the extruded strip is subjected to a first drying and a first calcination to obtain a carrier;
[0039] S2. The carrier is impregnated with an aqueous solution of a compound containing a Group VIII metal and a Group VIB metal to obtain an impregnated carrier; the impregnated carrier is then subjected to a second drying and activation treatment.
[0040] According to this disclosure, the weight ratio of the matrix to the molecular sieve can be 5-60:40-95.
[0041] According to this disclosure, in step S1, the conditions for the first drying treatment include: a drying temperature of 80-300℃, preferably 100-200℃; and a drying time of 1-12 hours, preferably 2-8 hours; the conditions for the first calcination include: a calcination temperature of 350-850℃, preferably 450-650℃; and a calcination time of 1-12 hours, preferably 2-6 hours; in step S2, the conditions for the impregnation include: an impregnation temperature of room temperature -150℃; and an impregnation time of 1-6 hours; the conditions for the second drying include: a temperature of 100-300℃, preferably 100-150℃; and a time of 2-8 hours; the conditions for the activation treatment include: a temperature of 100-350℃, preferably 120-250℃; and a time of 1-12 hours, preferably 2-6 hours.
[0042] A third aspect of this disclosure provides a method for removing aromatics from a diesel fraction. The method includes contacting the diesel fraction and hydrogen with the aforementioned hydrocracking catalyst and performing a hydrocracking reaction. The hydrocracking catalyst of this disclosure enhances the removal of aromatics from the diesel fraction by regulating the matching between the molecular sieve pore structure and the molecular structure of bicyclic aromatic hydrocarbons, thereby promoting the diffusion, adsorption, and reaction of aromatics.
[0043] The present disclosure is further illustrated by the following examples, but the present disclosure is not limited thereto. Unless otherwise specified, all reagents used in the examples are chemically pure.
[0044] The adsorption molar ratio test method disclosed herein is as follows: First, accurately measure 100 mL of tetrahydronaphthalene solution (at room temperature), then add a quantitative amount of molecular sieve material (5 g), and stir under an inert gas (N2) atmosphere at 1 atm and 360°C for 10 hours in a sealed environment. Then filter, re-adjust the filtrate to the correct volume, cool to room temperature, and measure the solution volume again using a graduated cylinder. The pore volume is determined by BET, and the acidity is determined by NH3-TPD.
[0045] The properties of molecular sieves are listed in Table 1.
[0046] Example 1
[0047] 171.4 g of pseudoboehmite (Catalyst Changling Branch) with a dry basis of 70% and 97.6 g of ITQ-37 molecular sieve with a dry basis of 82% were weighed and extruded into butterfly-shaped support strips with an outer circle diameter of 1.6 mm on an extruder. The strips were dried at 120°C for 3 hours and calcined at 600°C for 4 hours to obtain catalyst support Z1.
[0048] 100 g of support Z1 was impregnated for 3 hours in 81 mL of a mixed solution of ammonium metatungstate, basic nickel carbonate, and phosphoric acid containing 271.6 g / L WO3, 24.7 g / L NiO, and 12.3 g / L P2O5, respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 2 hours to obtain catalyst C1. The composition based on the catalyst is shown in Table 2.
[0049] Example 2
[0050] 171.4 g of pseudoboehmite (Catalyst Changling Branch) with a dry basis of 70% and 98.8 g of OSB-1 molecular sieve with a dry basis of 81% were weighed and extruded into butterfly-shaped support strips with an outer circle diameter of 1.6 mm on an extruder. The strips were dried at 120°C for 3 hours and calcined at 600°C for 4 hours to obtain catalyst support Z2.
[0051] 100 g of support Z2 was impregnated for 3 hours in 90 mL of a mixed solution of ammonium metatungstate, basic nickel carbonate, and phosphoric acid containing 244.4 g / L WO3, 2.2 g / L NiO2, and 11.1 g / L P2O5, respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 2 hours to obtain catalyst C2. The composition based on the catalyst is shown in Table 2.
[0052] Example 3
[0053] 171.4 g of pseudoboehmite (Catalyst Changling Branch) with a dry basis of 70% and 105.3 g of EMC-2 molecular sieve with a dry basis of 76% were weighed and extruded into butterfly-shaped support strips with an outer circle diameter of 1.6 mm on an extruder. The strips were dried at 120°C for 3 hours and calcined at 600°C for 4 hours to obtain catalyst support Z3.
[0054] 100 g of support Z3 was impregnated for 3 hours in 78 mL of a mixed solution of ammonium metatungstate, basic nickel carbonate, and phosphoric acid containing 282.0 g / L WO3, 25.6 g / L NiO, and 12.8 g / L P2O5, respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 2 hours to obtain catalyst C3. The composition based on the catalyst is shown in Table 2.
[0055] Example 4
[0056] 185.7 g of pseudoboehmite (Catalyst Changling Branch) with a dry basis of 70% and 85.4 g of ITQ-37 molecular sieve with a dry basis of 82% were weighed and extruded into butterfly-shaped support strips with an outer circle diameter of 1.6 mm on an extruder. The strips were dried at 120°C for 3 hours and calcined at 600°C for 4 hours to obtain catalyst support Z4.
[0057] 100 g of support Z4 was impregnated for 3 hours in 85 mL of a mixed solution containing molybdenum trioxide, basic nickel carbonate, and phosphoric acid, with molybdenum O3 (176.5 g / L), NiO (35.3 g / L), and P2O5 (35.3 g / L), respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 2 hours to obtain catalyst C4. The composition based on the catalyst is shown in Table 2.
[0058] Example 5
[0059] 100 g of support Z4 was impregnated for 3 hours in 85 mL of a mixed solution containing molybdenum trioxide, basic cobalt carbonate, and phosphoric acid, with molybdenum O3 (176.5 g / L), cobalt O (35.3 g / L), and P2O5 (35.3 g / L), respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 2 hours to obtain catalyst C5. The composition based on the catalyst is shown in Table 2.
[0060] Example 6
[0061] 100 g of support Z4 was impregnated for 3 hours in 85 mL of a mixed solution containing ammonium metatungstate, basic nickel carbonate, phosphoric acid, and citric acid, with WO3 329.4 g / L, NiO 35.3 g / L, and P2O5 23.4 g / L respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 3 hours to obtain catalyst C6. The composition based on the catalyst is shown in Table 2.
[0062] Example 7
[0063] 114.3 g of boehmite (Catalyst Changling Branch) with a dry basis of 70%, 85.4 g of ITQ-37 molecular sieve with a dry basis of 82%, and 65.8 g of silica-alumina (Sasol GmbH, Germany) with a dry basis of 76% were weighed and mixed evenly. The mixture was then extruded into a butterfly-shaped support strip with an outer circle diameter of 1.6 mm on an extruder. The strip was dried at 120°C for 3 hours and calcined at 600°C for 4 hours to obtain catalyst support Z7.
[0064] 100 g of support Z7 was impregnated for 3 hours in 82 mL of a mixed solution containing molybdenum trioxide, basic nickel carbonate, and phosphoric acid, with molybdenum O3 (182.9 g / L), NiO (36.6 g / L), and P2O5 (36.6 g / L), respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 2 hours to obtain catalyst C7. The composition based on the catalyst is shown in Table 2.
[0065] Comparative Example 1
[0066] 171.4 g of pseudoboehmite (Catalyst Changling Branch) with a dry basis of 70% and 94.1 g of Y molecular sieve with a dry basis of 85% were weighed and extruded into butterfly-shaped support strips with an outer circle diameter of 1.6 mm on an extruder. The strips were dried at 120°C for 3 hours and calcined at 600°C for 4 hours to obtain catalyst support Zd.
[0067] 100 g of support Zd was impregnated for 3 hours in 80 mL of a mixed solution of ammonium metatungstate, basic nickel carbonate, and phosphoric acid containing 275.0 g / L WO3, 25.0 g / L NiO, and 12.5 g / L P2O5, respectively. After drying at 120 °C for 3 hours, it was activated at 200 °C for 2 hours to obtain catalyst DC. The composition based on the catalyst is shown in Table 2.
[0068] Table 1
[0069] ITQ-37 0.501 2.122 1.39 OSB-1 0.611 1.711 1.25 EMC-2 0.512 1.857 1.31 Y 0.510 1.522 1.00
[0070] Table 2
[0071]
[0072]
[0073] Test Example 1
[0074] Using 99% pure tetrahydronaphthalene as raw material (analytical grade), the reaction performance of catalysts C1, C2, C3, and DC provided by this invention was evaluated in a micro-fixed bed reactor. The catalyst loading was 1.0 g, and the reaction conditions were 330℃~390℃ and 4.0 MPa. For better comparison, the following two performance indicators are given and defined, and the results are listed in Table 3.
[0075]
[0076] Table 3
[0077] Conversion rate Baseline * 116.0% Baseline * 140.4% Baseline * 102.7% benchmark
[0078] As can be seen from Table 3, compared with existing catalysts, the catalyst provided in this disclosure can achieve a higher conversion rate in the tetrahydronaphthalene hydrocracking process, which is beneficial for deep dearomatization of diesel fuel and obtaining high-quality products.
[0079] The preferred embodiments of this disclosure have been described in detail above. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0080] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0081] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.
Claims
1. A hydrocracking catalyst for bicyclic aromatic hydrocarbons, characterized in that, The hydrocracking catalyst comprises a support and an active metal component supported on the support; the active metal component comprises Group VIII and Group VIB metal elements; the support is composed of an acidic component and a matrix, wherein the acidic component is a molecular sieve with an N value of 1-100 and greater than 1; the pore volume of the molecular sieve is 0.4-0.8 cm³. 3 / g, acid density is 0.8-2.5 μmol / m 2 The molecular sieve is selected from at least one of ITQ-40 molecular sieve, ITQ-44 molecular sieve, ITQ-53 molecular sieve, ITQ-54 molecular sieve, OSB-1 molecular sieve, and EMC-2 molecular sieve. The N value of a certain molecular sieve to be tested is defined as the ratio of the amount of bicyclic aromatic hydrocarbons and their derivatives adsorbed by the molecular sieve to the amount of bicyclic aromatic hydrocarbons and their derivatives adsorbed by the standard molecular sieve. The standard molecular sieve is HY molecular sieve, and the molar ratio of SiO2 to Al2O in the standard molecular sieve is 5.4, and the cell constant is 24.60 Å.
2. The hydrocracking catalyst according to claim 1, wherein, The N value of the molecular sieve is 1-20 and greater than 1.
3. The hydrocracking catalyst according to claim 1, wherein, Based on the total weight of the carrier, the content of the acidic component is 5-60% by weight; the content of the matrix is 40-95% by weight.
4. The hydrocracking catalyst according to claim 3, wherein, Based on the total weight of the carrier, the content of the acidic component is 10-45% by weight; the content of the matrix is 55-90% by weight.
5. The hydrocracking catalyst according to claim 1, wherein, Based on the total weight of the catalyst, the hydrocracking catalyst contains 1-10% by weight of Group VIII metals and 2-40% by weight of Group VIB metals, calculated as oxides.
6. The hydrocracking catalyst according to claim 5, wherein, Based on the total weight of the catalyst, the hydrocracking catalyst contains 1-6% by weight of Group VIII metal components and 5-35% by weight of Group VIB metal components, calculated as oxides.
7. The hydrocracking catalyst according to claim 1, wherein, The matrix is selected from at least one of alumina, silicon oxide, and silicon-alumina.
8. A method for preparing the hydrocracking catalyst according to any one of claims 1-7, characterized in that, The method includes the following steps: S1. The matrix and molecular sieve are mixed, kneaded, and extruded to obtain an extruded strip; the extruded strip is subjected to a first drying and a first calcination to obtain a carrier; S2. Impregnate the support with an aqueous solution of a compound containing a Group VIII metal and a Group VIB metal to obtain an impregnated support; subject the impregnated support to a second drying and activation treatment to obtain a hydrocracking catalyst.
9. The method according to claim 8, wherein, The weight ratio of the matrix to the molecular sieve is 5-60:40-95.
10. The method according to claim 8, wherein, In step S1, the conditions for the first drying treatment include: a drying temperature of 80-300℃ and a drying time of 1-12 hours; the conditions for the first calcination include: a calcination temperature of 350-850℃ and a calcination time of 1-12 hours. In step S2, the conditions for impregnation include: an impregnation temperature of room temperature to 150°C and an impregnation time of 1 to 6 hours; the conditions for the second drying include: a temperature of 100 to 300°C and a time of 2 to 8 hours; and the conditions for the activation treatment include: a temperature of 100 to 350°C and a time of 1 to 12 hours.
11. The method according to claim 10, wherein, In step S1, the conditions for the first drying treatment include: a drying temperature of 100-200℃ and a drying time of 2-8 hours; the conditions for the first calcination include: a calcination temperature of 450-650℃ and a calcination time of 2-6 hours. In step S2, the conditions for the second drying include a temperature of 100-150°C; the conditions for the activation treatment include a temperature of 120-250°C and a time of 2-6 hours.
12. A method for removing aromatics from diesel fractions, characterized in that, The method includes: contacting the diesel fraction and hydrogen with the hydrocracking catalyst according to any one of claims 1-11 and carrying out a hydrocracking reaction.
Citation Information
Patent Citations
Hydrocracking catalysts, their preparation methods, and hydrocracking reaction methods
CN105457671B
Hydroprocessing catalyst and method of making the same
US20110000824A1
Hydroalkylation of aromatic hydrocarbons
WO1994008712A1